The Effect of Job Satisfaction and Organizational Commitment on Turnover Intention among Employees of "X" Tourist Lodge - Galvin Christian Lukyanto; Akhmad Fauzi (International Journal of Economics (IJEC), 2023)
This research aimed to examine whether the model of job satisfaction and organizational commitment contributed to turnover intention among employees of "X" Tourist Lodge. The population for this study consisted of employees of "X" Tourist Lodge. The sampling method used was saturation sampling, where the entire population became the sample for this study, with a total of 36 respondents. The data collection method used in this study was a survey, and a partial least square was used as the data analysis tool. The results of the research showed that job satisfaction and organizational commitment had a significant effect on turnover intention among employees of "X" Tourist Lodge. Lower levels of job satisfaction among employees led to an increase in their desire to quit their jobs. Similarly, lower levels of organizational commitment among employees in achieving organizational goals led to an increased desire among employees to leave their jobs at "X" Tourist Lodge.